The Potential of Liquid Organic Fertilizer for Hydroponic Nutrition: A Systematic Literature Review - Syamsia, Syamsia (ITScience (Information Technology and Science), 2024)
Nutrients are the main component in a hydroponic system. Liquid organic fertilizer has the potential to be a source of hydroponic nutrition because it can be made from agricultural waste through a fermentation process using local microorganisms. The aim of the research is to analyze articles that use the theme of liquid organic fertilizer and describe various topics that are relevant and have novelties to be developed in future research. The bibiometric analysis used in the research used the 2019-2023 literature. The data collection method uses dimensions with the keyword